The impact of Lyme disease on quality of life and multiorgan function, diagnosis, late stages of the disease and PTLDS - Dutka, Martyna; Bernacki, Radosław; Bernacki, Piotr; Zardzewiały, Witold; Skrzyńska, Klaudia; Zaremskyi, Oleksii; Fuszara, Kamil; Mordasiewicz, Dominika; Mendyk, Krzysztof (Quality in Sport, 2024)
Introduction and purpose of the work: Lyme disease is the most common tick-borne disease in the world. It is caused by bacteria of the Borrelia genus. It is transmitted by ticks of the Ixodes genus. The disease caused by these bacteria can affect many organs of the human body. Knowledge about diagnosis, form of the disease and treatment is necessary because this disease entity can often be encountered in clinical practice. The aim of the study is to present information on available diagnostic methods and to describe the organ form of the disease, distinguishing: articular form, cardiac form and neuroborreliosis, based on a review of the current literature. Review methods: The review is based on 20 articles obtained from PubMed databases, using the keywords: "Lyme joint disease", "neuroborrelia", "Lyme heart disease". Published between 2000 and 2023. Brief description of the state of knowledge: Lyme disease most often causes symptoms affecting the skin, musculoskeletal system, heart muscle, and nervous system. The diagnosis of the disease is based on the clinical symptoms presented by the patient. The key symptom of the disease is the presence of erythema migrans (EM). The articular form of Lyme disease is characterized by an ongoing inflammatory process located within the joint. It is located within large ponds. The most common cardiac form of the disease is self-limiting cardiac inflammation caused by Lyme disease. However, in the course of neuroborreliosis, meningitis is observed. Treatment is based on antibiotic therapy. Conclusions: Lyme disease is a life-threatening disease. It can cause non-specific symptoms, so it is important to diagnose it as early as possible and treat it to prevent progression.